Sodium‐glucose cotransporter 2 inhibitors are associated with reduced risk of mortality and readmissions in heart failure - Patric Karlström; Aldina Pivodic; Ulf Dahlström; Michael Fu (ESC Heart Failure, 2024)
Abstract Aims Compelling evidence from randomized trials has shown that sodium‐glucose cotransporter 2 inhibitors (SGLT2is) are effective in heart failure (HF) across the spectrum of left ventricular ejection fractions. However, there are very few studies with real‐world data. Methods and results A retrospective cohort analysis was performed based on patient‐level data from the Swedish Heart Failure Registry (SwedeHF) linked with three other national registers. Patients included had an index registration between 3 September 2013 and 31 December 2020 in SwedeHF and were on treatment with guideline‐recommended therapy without or with SGLT2i 3 months before or 6 months after their index registration. Endpoints were mortality or readmissions. Association between the use of SGLT2i and endpoints was studied using adjusted Cox models. In the overall cohort, 796/22 405 patients were included with/without SGLT2i. In patients with SGLT2i, 93.5% had diabetes mellitus. In the overall cohort, SGLT2i was statistically significantly associated with all‐cause mortality {hazard ratio [HR]: 0.61 [95% confidence interval (CI) 0.48–0.79], P < 0.0001}, cardiovascular mortality [HR: 0.29 (95% CI 0.17–0.50), P < 0.0001], cardiovascular mortality or HF readmission [HR: 0.89 (95% CI 0.80–1.00), P = 0.046], and all‐cause readmissions [HR: 0.90 (95% CI 0.81–0.99), P = 0.038]. Similar results were obtained for the diabetes cohort. However, no association with cause‐specific readmissions was observed. Conclusions This nationwide real‐world study indicates that patients with HF, in which majority coexisted with diabetes mellitus, who received SGLT2i were statistically significantly associated with lower risk for all‐cause mortality, cardiovascular mortality, cardiovascular mortality or HF readmissions, and all‐cause readmissions, in line with the randomized trials assessing SGLT2i.